An integrated EHS-based risk assessment framework for hazardous substance storage: regulatory gap analysis in Thailand - Hengheng Jarunongkran; Therdpong Daengsi (Institute of Advanced Engineering and Science, 2026)
This study examines hazardous substance storage risk assessment within the environmental, health, and safety (EHS) framework, focusing on Thailand’s regulatory context. Using a systematic review and comparative regulatory analysis, the research evaluates existing risk assessment methodologies and identifies structural and implementation gaps in current practices. The findings reveal deficiencies in the integration of toxicological data with legal requirements, fragmented regulatory enforcement, limited standardization, and insufficient practical tools for workplace application. A comparative assessment of international frameworks, including European Union Registration, Evaluation, Authorization, and Restriction of Chemicals (EU REACH), United States Occupational Safety and Health Administration (US OSHA), and Japan’s Chemical Substances Control Law (CSCL), highlights best practices in proactive risk management and transparency. Based on these insights, the study proposes an integrated EHS-based risk assessment framework that aligns Department of Industrial Works (DIW) regulations with international standards such as ISO 14001, ISO 45001, and globally harmonized system (GHS). The proposed model supports proactive risk identification, regulatory coherence, and improved stakeholder awareness, contributing to enhanced chemical safety governance and ASEAN harmonization.